2018
DOI: 10.3791/56307
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Aligned Steel Fiber Reinforced Cementitious Composite and Its Flexural Behavior

Abstract: The aim of this work is to present an approach, inspired by the way in which a compass needle maintains a consistent orientation under the action of the Earth's magnetic field, for manufacturing a cementitious composite reinforced with aligned steel fibers. Aligned steel fiber reinforced cementitious composites (ASFRC) were prepared by applying a uniform electromagnetic field to fresh mortar containing short steel fibers, whereby the short steel fibers were driven to rotate in alignment with the magnetic field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…After finishing the fracture test, the specimens were broken into two sections along the crack at the notch. In order to analyze the orientation of steel fibers, the manual fibercounting method was used to record the angle between the steel fiber and the axis of the specimen according to [32]. The angles were divided into four zones, namely, 0-15 • , 15-45 • , 45-75 • , and 75-90 • .…”
Section: Evaluation Of Steel Fiber Orientationmentioning
confidence: 99%
“…After finishing the fracture test, the specimens were broken into two sections along the crack at the notch. In order to analyze the orientation of steel fibers, the manual fibercounting method was used to record the angle between the steel fiber and the axis of the specimen according to [32]. The angles were divided into four zones, namely, 0-15 • , 15-45 • , 45-75 • , and 75-90 • .…”
Section: Evaluation Of Steel Fiber Orientationmentioning
confidence: 99%
“…In this method, the mixture is placed inside an empty interior chamber looped by a square solenoid coil and the steel fibers are aligned by the uniform magnetic field offered by the solenoid. The orientation coefficient of ASFRC prepared by the square solenoid coil can exceed 0.9, and the ASFRC exhibits flexural strengths of 88% greater than SFRC when the fiber volume fractions are 0.8% (Mu et al, 2018). According to Qing et al (Qing et al, 2019), the dosage of steel fibers can be decreased by at least 40% if the tensile strength of ASFRC utilizing aligned steel fiber technology is equal to that of SFRC (it may even be somewhat greater).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the distribution direction of steel fibers can be adjusted by changing the pouring method and pouring sequence [7][8][9] as well as applying an electromagnetic field. [10][11][12] Yoo et al 13,14 prepared reactive powder concrete (RPC) members with a maximum fiber orientation efficiency factor of 0.66 by pouring concrete at the end of a test mold and letting it flow freely to fill the mold. The quasi-static loading test results indicated that larger fiber orientation efficiency factor produced higher flexural strength, deformation capacity, and increased toughness.…”
Section: Introductionmentioning
confidence: 99%
“…The three-point bending test results showed a tenfold post-cracking flexural strength difference for cutting angles of 0 and 90 relative to the radial direction. Mu et al [10][11][12] designed a small electromagnetic field device to adjust the fiber distribution, to which a steel fiber-reinforced cement mortar with a fiber orientation efficiency factor of about 90% was fabricated. After adjusting the fiber direction, the flexural tensile strength of the specimen could be increased by 146% and the residual strength could be increased by 150% and 200% at deflections of l/150 and l/600, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation